Econometrics Model of Economic Growth in East Java Province with Dynamic Panel Data through Generalized Method of Moment (GMM) Approach - Joko Hadi Susilo; Luthfi Ibnu Tsani; Herianto Herianto; M Kholilurrohman (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
Increasing the rate of economic growth is one of the biggest goals for an area, because it affects macroeconomic conditions in the aggregate especially the level of public welfare. Law Number 32 of 2004 becomes empirical evidence that there is a transfer of responsibility from the central government to regional governments in carrying out economic development. This research is conducted to determine the condition of economic growth in East Java Province with a population of 29 districts and 9 cities in the 2014-2018 observation period, the number of samples was 190 samples. The data analysis technique is carried out through the econometrics model with two stages, namely conducting a simultaneous regression analysis of the ordinary least square method, then for the second stage, an Arellano-Bond Generalized Method of Moment (GMM) analysis is carried out on the grounds that many economic variables are dynamic, This means that the value of a variable can be influenced by the value of other variables and is influenced by the value of the variable concerned in the past or previous period,in addition to knowing the short-term and long-term effects of economic growth. The findings of the study reveal that simultaneous economic growth in East Java Province is influenced by agglomeration, fiscal decentralization, poverty rates and human development index. Based on the results of the generalized method of moment arellano-bond analysis, the researchers find that fiscal decentralization have a partial effect on economic growth in the province of East Java with the impact of the elasticity of short-term and long-term economic growth values. In addition, researchers find that economic growth in East Java Province is influenced by the value of the variable itself (economic growth) in the previous period.